2021–2022 Florida Citrus Production Guide: Best Management Practices for Soil-Applied Agricultural Chemicals - Lauren Marie Diepenbrock; Davie M. Kadyampakeni; Larry W. Duncan (EDIS, 2021)
Reviewed March 2021. There are no changes in recommendation from 2020.